Real-time monitoring of indoor air corrosivity in cultural heritage institutions with metallic electrical resistance sensors. (1st April 2013) - Prosek, T.; Kouril, M.; Dubus, M.; Taube, M.; Hubert, V.; Scheffel, B.; Degres, Y.; Jouannic, M.; Thierry, D.
<x xml:space="preserve">Abstract</x> A system for continuous monitoring of atmospheric corrosivity has been developed. An electronic unit measures and records changes in the electrical resistance of a thin metal track applied on an insulating substrate. If the metal corrodes, the effective cross sectional area of the track decreases and the electrical resistance increases. Sensors made of silver, copper, iron/steel, zinc, lead, tin, aluminium, bronze, and brass at thicknesses from 50 nm to 250 µm were tailored for environments with different corrosivities. The developed technology proved capable of providing high sensitivity, allowing for real-time corrosion monitoring even in low-corrosive indoor cultural heritage facilities. Laboratory tests showed good reproducibility with the standard deviation of parallel measurements at less than ±20% for metals which corrode uniformly in the tested environments. Several examples selected from a broad testing programme in partner museums, libraries, and other institutions show successful applications of the logger system for characterization of air quality control in indoor locations, during transport and in temporary exhibitions; assessment of new buildings and storage facilities; and fundamental studies of optimal conservation and storage procedures. A first outline of a classification system for lead, which is particularly sensitive to the presence of carboxylic acids, is given. The technique has a large potential as an independent method for monitoring air quality in facilities displaying and storing valuable objects of cultural heritage.